Myeloid cells in alcoholic liver diseases: Mechanism and prospect - Xu, Wentao; Wu, Miaomiao; Chen, Bangjie; Wang, Hua (Frontiers in Immunology, 2022)
Alcoholic liver disease (ALD) is a leading chronic liver disease in which immune cells play a vital role. Myeloid cells have been extensively studied in ALD, including granulocytes, macrophages, monocytes, and dendritic cells, which are involved in the occurrence and progression of steatosis, inflammation, fibrosis, and eventual cirrhosis. These cells can be popularly targeted and regulated by factors from different sources, including cytokines secreted by other cells, extracellular vesicles, and substances in serum—for example, infiltration of monocytes or neutrophils, activation of Kupffer cells, and polarization of macrophages. These processes can affect and change the function and phenotype of myeloid cells. Here we mainly review the key mediators that affect the infiltration and function of mainly myeloid cells in ALD as well as their regulatory mechanisms on target cells, which may provide novel immunotherapeutic approaches. The single-cell multimodal omics of myeloid cells is also discussed to help transform them into basic research or therapeutic strategy of ALD clinically.